Continuous wave three-dimensional chiral perovskite laser and preparation method thereof
The perovskite material processed by chiral solution is uniformly distributed in the optical microcavity, combined with the design of the spacer layer and the reflective layer, the problem of three-dimensional chiral perovskite laser emission is solved, and efficient circular polarization laser emission is achieved.
Patent Information
- Application Number
- CN202411786181.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The prior art is difficult to achieve laser emission of chiral organic-inorganic metal halide perovskites in a three-dimensional structure, and low-dimensional chiral perovskite materials have low laser emission efficiency at room temperature.
Perovskite material that is treated with chiral solution is used to uniformly distribute the perovskite material in the optical microcavity to form a gain medium, and through the design of the spacer layer and the reflective layer, the interaction between the optical microcavity is enhanced to achieve laser emission.
High-quality circular polarized laser emission in three-dimensional structures is achieved, with good time and spatial coherence, with a threshold of 12.73μJ/cm2 and a multimode laser threshold of 0.6 W/cm2.
Smart Images

Figure CN119275704B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optoelectronic devices, and in particular to a continuous wave three-dimensional chiral perovskite laser and a preparation method thereof. Background Art
[0002] Circularly polarized (CP) lasers, with their optical activity and high coherence, are crucial for numerous applications, covering technologies such as nanophotonics, quantum optics and communications, biophysics and chemistry, medical diagnostics, chiral sensing, information encryption, and three-dimensional (3D) displays. They are not only a key to exploring chirality-related phenomena in light-matter interactions, but also an effective means to manipulate photons, phonons, charge carriers, and spin states. Conventional circularly polarized lasers require bulky polarization optical components and complex heterogeneous integration, limiting their miniaturization. In contrast, recently developed near-field polarization strategies, such as metasurfaces and low-dimensional materials, have achieved circularly polarized lasers at the nanoscale, as well as the integration of space-momentum dimensions, providing unlimited possibilities for new physical phenomena and promising applications.
[0003] Among all low-dimensional materials, chiral hybrid organic-inorganic metal halide perovskites (HOIPs) have attracted much attention due to their unique optoelectronic and electromagnetic properties, which has opened up a research boom in organic-inorganic metal halide perovskites in the fields of chiral optoelectronics, chiral spin electronics, ferroelectrics, and nonlinear optics. At the same time, even among non-chiral similar materials, they have become one of the best candidate materials for high-performance laser devices due to their low laser threshold, high gain, flexibility, tunable laser emission covering the blue light to near-infrared region, low temperature and large-scale solution processing, and the ability of non-epitaxial heterogeneous integration in various shapes and scales (from nanocrystals, nanowires to bulks). Therefore, combining chiral optical properties with the laser properties of perovskites is expected to open up an exciting new direction.
[0004] However, there are currently huge challenges in achieving chiral lasers in chiral organic-inorganic metal halide perovskites. On the one hand, in the literature reports so far, chiral organic-inorganic metal halide perovskites can only be achieved in low-dimensional (0D / 1D / 2D) perovskites. However, there are strong Auger recombination and exciton-phonon interactions in low-dimensional chiral perovskites, which seriously hinder the realization of high photoluminescence quantum yield (PLQY) and optical gain at room temperature. In addition, all low-dimensional chiral perovskite materials developed previously mainly rely on weak intermolecular interactions, such as hydrogen bonds (NH...Br / I) between chiral ligands and perovskite inorganic frameworks, which limits the feasibility of achieving circularly polarized (CP) lasing at room temperature. On the other hand, although three-dimensional organic-inorganic metal halide perovskites (ABX3) can achieve optical gain and laser emission at room temperature, it is still in the theoretical prediction stage to give chiral properties to three-dimensional structured perovskites. This is due to the tolerance constraints at the A-site ions. No chiral cations can stably exist at the A site of the three-dimensional framework at room temperature. Compared with low-dimensional chiral perovskites, the low exciton binding energy and high carrier transport capacity of three-dimensional organic-inorganic metal halide perovskites are very attractive for chiral optoelectronics. Therefore, it is urgent to develop new material synthesis strategies to obtain three-dimensional chiral organic-inorganic metal halide perovskites and realize chiral laser emission. Summary of the invention
[0005] The purpose of the embodiments of the present application is to provide a continuous wave three-dimensional chiral perovskite laser and a method for preparing the same in order to address the problems existing in the prior art.
[0006] According to a first aspect of an embodiment of the present application, a continuous wave three-dimensional chiral perovskite laser is provided, comprising an optical microcavity, a gain medium, and a spacer layer, wherein the gain medium is sandwiched between the optical microcavity and the spacer layer, and a reflective layer is plated on the spacer layer:
[0007] The gain medium is a perovskite material or a mixed material containing a perovskite material after being treated with a chiral solution, and is uniformly distributed in the optical microcavity in the form of a thin film, microcrystal, nanocrystal, quantum dot or single crystal, with a thickness of 10nm to 1mm;
[0008] The composition of the perovskite material is A'2A n-1 B n X 3n+1 Or ABX3, wherein A' is an organic amine ion, A is a monovalent cation, B is a divalent metal cation, X is an anion, and n is a positive integer; A' is phenethylamine PEA + , butylamine BA + , ethylamine EA +, S / R-bromo-1-phenylethylamine s-Br-MBA, S-α-methylbenzylamine s-MBA, R-1-naphthylethylamine s-1-NEA or a combination thereof; A cesium ion Cs + , methylamine ion MA + , formamidinium ion FA + , ethylamine ion EA + , guanidine ion GA + 、Isopropylamine ion IPA + One or more combinations thereof; B is lead ion Pb 2+ 、Sn 2+ 、Ge 2+ 、Indium ion In 2+ 、Bi ion 2+ One or more combinations of; X is a chloride ion Cl - 、Br - 、Iodide ion I - A combination of one or more of .
[0009] Furthermore: the mixed material includes one or more of organic materials, quantum dot materials, oxide materials, III-V materials, II-VI materials, and rare earth materials to reduce the defect density in the perovskite material and improve the crystal quality.
[0010] Furthermore: the chiral solution is prepared by dissolving one or more of a chiral inorganic material, a chiral organic material, and a chiral polymer material in tetrahydrofuran or isopropanol to transfer chirality to the perovskite material.
[0011] Furthermore: the chiral inorganic material is R, S-mandelic acid, R, S-camphorsulfonic acid, R, S-pyroglutamic acid; the chiral organic material is amino acids (alanine, valine), chiral fluorescent molecules (fluorescein, rhodamine, boroazacyclopentadiene); the chiral supramolecular polymer material is one or more of the following: helical polyurethane supramolecular polymer (trityl methyl acrylate), helical peptide supramolecular polymer (α-helical peptide supramolecular polymer) to transfer chirality to the perovskite material.
[0012] Furthermore: the type of the optical microcavity is a distributed Bragg reflector (DBR), a distributed feedback Bragg grating (DFB), a photonic crystal (PC), a continuous bound state structure (BIC), a topological photonic crystal (TC) or a whispering gallery mode (WGM) microcavity to enhance the interaction between the gain medium and the light to generate laser.
[0013] Furthermore, the spacer layer is formed of a polymer, and the polymer is polymethyl methacrylate PMMA, polyethylene glycol PEG, polyethylene oxide PEO or polyvinyl pyrrolidone PVP, so as to reduce the optical loss in the microcavity and increase the cavity length.
[0014] According to a second aspect of an embodiment of the present application, a method for preparing a continuous wave three-dimensional chiral perovskite laser is provided, which is used to prepare the continuous wave chiral perovskite laser as described in the first aspect, comprising:
[0015] Fabrication of optical microcavities;
[0016] Preparation of gain medium: A'X, AX, BX2 are mixed in a solvent to obtain a perovskite precursor solution; the perovskite precursor solution is spin-coated or drop-coated on the bottom optical microcavity, annealed, and crystallized; the chiral solution is drop-coated on the crystallized perovskite material for post-treatment to obtain a gain medium;
[0017] Spin coating the polymer on the gain medium to form a spacer layer;
[0018] The vacuum is applied, and a reflective layer is formed on the spacer layer by thermal evaporation.
[0019] Furthermore: on quartz, sapphire or flexible substrate polyethylene terephthalate (PET), a multilayer silicon dioxide / tantalum pentoxide dielectric layer is deposited by sputtering or electron beam evaporation to form a distributed Bragg reflector with high reflectivity as the bottom reflection layer of the laser; the thickness of each dielectric layer is λ / 4n, where λ is the central wavelength of the gain medium light emission and n is the refractive index of the dielectric layer material.
[0020] Furthermore: a metal silver film with a thickness of 200-500 nm is deposited on the spacer layer by thermal evaporation to provide high reflectivity, that is, to form a top reflective layer of the laser, thereby forming a vertical microcavity surface emitting laser VCSEL structure.
[0021] Furthermore: the solvent is a mixture of any one or more of N,N-dimethylformamide DMF, dimethyl sulfoxide DMSO, γ-butyrolactone GBL, and dimethylacetamide DMA; a molecular additive is also added to the precursor solution, and the molecular additive is a mixture of one or more of polymers, small molecules, and oxides to passivate defects in the perovskite film and reduce non-radiative recombination centers.
[0022] The technical solution provided by the embodiments of the present application may have the following beneficial effects:
[0023] 1. This application adopts a simple, easy-to-operate, and low-cost method of post-treating perovskite crystals with a chiral solution to prepare high-quality perovskite gain media. While passivating the surface defects of the perovskite crystal, it can form stable strong covalent bonds or ionic bonds through intramolecular forces, and conduct the chiral spin electrons in the chiral material to the non-chiral perovskite crystal, achieving circularly polarized luminescence, and the asymmetry factor reaches 8.5×10 -3 (-8×10 -3 ).
[0024] 2. The post-processed perovskite crystals of this application can generate stimulated radiation amplification under femtosecond laser excitation, and the threshold is 12.73μJ / cm 2 The asymmetry factor of the emission is enlarged to 0.054 near the threshold. Combined with high-quality optical microcavity, it can form laser emission under continuous wave laser excitation, and the multi-mode laser threshold is 0.6 W / cm 2 .
[0025] 3. The laser prepared in this application has good temporal and spatial coherence and good circular polarization characteristics, and can be further used in technical fields such as quantum optics and communications, biophysics and chemistry, medical diagnosis, chiral sensing, information encryption, and three-dimensional (3D) display.
[0026] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0028] Figure 1 Schematic diagram of the preparation of the three-dimensional chiral perovskite film prepared in Example 1 and the chirality generation mechanism;
[0029] Figure 2 The stimulated emission amplification and chiral asymmetry factor characterization diagram of the three-dimensional chiral perovskite film prepared in Example 1;
[0030] Figure 3 This is the preparation and laser characterization diagram of the continuous wave chiral three-dimensional perovskite laser prepared in Example 1. DETAILED DESCRIPTION
[0031] Exemplary embodiments will now be described in detail, examples of which are shown in the accompanying drawings. The implementations described in the following exemplary embodiments are not intended to represent all implementations consistent with the present application.
[0032] Example 1
[0033] This embodiment introduces a method for preparing a continuous wave green chiral three-dimensional perovskite laser, and the specific steps are as follows:
[0034] Step 1: Place a 1.1 mm thick quartz glass substrate in an ultrasonic machine for cleaning. Place the cleaned and wiped quartz glass substrate in a sample holder. Place the sample holder with the quartz glass substrate in an electron beam coating machine for vacuum treatment. When the vacuum degree reaches 4×10 -4 Pa, SiO2 and Ta3O5 are evaporated on a quartz glass substrate in sequence, 7 groups of evaporation, the evaporation rate is controlled at 0.4nm / s, and the COMSOL simulation software is used to calculate that the thickness of each layer of silicon dioxide to be deposited is 63.21nm, and the thickness of each layer of Ta3O5 is 93.57nm, forming a distributed Bragg reflector DBR with high reflectivity (>98%).
[0035] Step 2: Dissolve the materials with a molar ratio of (FABr + MABr + GABr + CsBr) : PbBr2 = 1.15:1-1:1 in a 1 mL DMF, DMSO mixed solvent to form a 0.5 mol mL -1 A perovskite precursor solution, wherein the ratio of DMF to DMSO is 4:1, and 2-10 mg / ml of molecular additives are also added to the precursor solution.
[0036] Step 3: Evenly drop 50 μL of the perovskite precursor solution on the DBR; adjust the coating time of the coating machine to 60 s, control the coating speed to 5000 r / min, and drip chlorobenzene solution as an anti-solvent at the top hole at 30 s after starting the coating; place the DBR coated with the perovskite precursor solution on a hot stage for annealing at 100 ° C for 10 minutes to form a 100 nm thick perovskite light-emitting layer, i.e., a perovskite film. In a specific implementation, dichloromethane, ether, or a solvent mixture (such as DMSO and dimethylformamide) is also used as an anti-solvent.
[0037] Step 4: 50 μL of R-MA mandelic acid chiral solution was added dropwise onto the perovskite film, the reaction time was 20 s, and the spin coating speed was controlled to be 5000 r / min to obtain a chiral solution to post-treat the perovskite film;
[0038] Step 5: Spin-coat a layer of PMMA as a spacer layer on the chiral solution post-treated perovskite film to enhance the cavity length. The concentration of the PMMA solution is 220 mg / ml, and the spin-coating speed is 5000 rpm. After spin-coating, heat on a hot stage at 120°C for 10 min for curing.
[0039] Step 6: Place the sample obtained in step 5 into a thermal evaporation coating machine for vacuum treatment. When the vacuum degree reaches 8×10 -4 Pa, metallic silver is evaporated on the sample with a thickness of 320nm to form a top reflective layer with a reflectivity of >99%. After the thermal evaporation is completed, the device is taken out of the evaporation chamber, and the laser preparation is completed.
[0040] The laser is placed on an inverted microscope platform, and a continuous laser with a wavelength of 343nm is focused onto the gain medium layer of the device through a 10X lens. A wheel-type attenuator is placed in front of the objective lens to adjust the excitation intensity. A polarizer is placed in front of the imaging spectrometer, and the angle of the polarizer is rotated to measure the polarization of the generated laser beam. The beam of the chiral laser device is split into two beams after passing through a beam splitter. The two beams are respectively introduced into a fiber-coupled single-photon detector to measure the temporal and spatial coherence of the beam.
[0041] Figure 1 The process of post-treating three-dimensional perovskite films using chiral mandelic acid. Compared with the bulky alkyl chains commonly used in traditional nanocrystal synthesis, the compact and highly acidic chiral mandelic acid molecules can penetrate and embed into large-sized perovskite crystals, breaking the large-sized crystals into smaller-sized crystals. The functional groups (hydroxyl, carboxyl) on mandelic acid can effectively bind to uncoordinated lead atoms or halogen vacancies through chemical reactions to passivate defects on the crystal surface. It is precisely because of the covalent bonds or ionic bonds formed by the electronic reaction between this non-chiral inorganic lattice and the chiral organic acid that the chiral electrons are transferred to the non-chiral inorganic framework, thereby achieving circularly polarized luminescence.
[0042] Figure 2 a and Figure 2 Figure b is the stimulated amplified spontaneous emission (ASE) characterization diagram of the perovskite film after treatment with chiral mandelic acid, which shows that the perovskite film after treatment with chiral acid can produce stimulated radiation amplification with a threshold of 12.73 uj / cm 2, which is the basis for realizing laser. In order to characterize whether the ASE signal of the chiral solution-processed perovskite film has circular polarization characteristics, a quarter-wave plate is used to convert the ASE signal from circular polarization (CP) to linear polarization (LP), and then the corresponding linear polarization signal is detected by changing the angle of the polarizer relative to the fast axis of the quarter-wave plate. Under the excitation of 343 nm linearly polarized laser, the linear polarizer is rotated to a fixed angle (+45° and -45°) relative to the fast axis of the quarter-wave plate, and the ASE signals of right-handed and left-handed circular polarization (R / L-CP) are converted into linearly polarized light signals and enter the fiber spectrometer. Figure 2 c and Figure 2 The d in the figure shows the intensity difference between (R / L-CP) ASE, which indicates that the ASE signal of the chiral acid post-treated perovskite film has circular polarization characteristics. In addition, to further prove the accuracy of the above results, as shown in Figure 2 e and Figure 2 As shown in f, the polarization-dependent ASE intensity of left-handed and right-handed chiral mandelic acid post-treated perovskite films was tested, and these intensity data showed periodic changes consistent with a sine function. The two sets of data present an almost perpendicular relationship, which strongly verifies the right-handed and left-handed circularly polarized characteristics of the ASE signal from the perovskite film treated with a chiral solution (R / S-MA). This series of experiments not only confirms the effect of chiral solutions on the polarization state of perovskite materials, but also demonstrates the polarization characteristics of the ASE signal of the perovskite film at different pump intensities through detailed spectral analysis and intensity measurements, especially the realization of circularly polarized ASE. These results provide new insights into chiral optoelectronics and laser technology, and emphasize the potential of chiral materials in controlling the polarization properties of light.
[0043] Based on the circularly polarized ASE achieved above, a chiral solution-processed perovskite film was spin-coated on the bottom distributed Bragg reflector (DBR) mirror, PMMA was spin-coated, and finally a silver mirror (320 nm) was evaporated on the top to prepare a vertical cavity surface emitting (VCSEL) green laser ( Figure 3 (a) The bottom DBRs consist of 7 pairs of alternating quarter-wavelength SiO2 / Ta2O5 dielectric layers to ensure high reflectivity (>98%). Since the perovskite film thickness is only about 100 nm, we added a polymethyl methacrylate (PMMA) spacer layer to increase the cavity length. Figure 3 b and Figure 3 The c in the figure shows the variation of laser intensity with pump power density and the variation of half-width with pump power density. The calculation shows that the laser threshold at 250K is 0.6W / cm 2 . Figure 3 The half-width at half maximum in the laser spectrum is 0.7 nm above the threshold value. Figure 3The e in the figure indicates that the laser obtained by the prepared device has good polarization characteristics. Figure 3 f and Figure 3 As shown in g, the spatial coherence of the laser is further characterized using a Michelson interferometer. It can be clearly seen that clear coherent fringes appear above the threshold, indicating that the laser has good spatial coherence. Figure 3 i in the figure is the spot shape of the output beam of the VCSEL device when it is excited above the threshold and projected onto a piece of paper at a distance of 10 cm. The beam is clear and consistent with a typical VCSEL beam ( Figure 3 h in ). Figure 3 The j and Figure 3 The k in the figure characterizes the circular polarization characteristics of the chiral solution-processed perovskite film in the perpendicular surface laser. These intensity data show periodic changes that are consistent with a sine function. In addition, the two sets of data show an almost perpendicular relationship, which strongly verifies that the laser signal in the laser has right-handed and left-handed circular polarization characteristics.
[0044] Example 2
[0045] This embodiment introduces a method for preparing a continuous wave green chiral three-dimensional perovskite laser, and the specific steps are as follows:
[0046] Step 1: Place a 1.1 mm thick quartz glass substrate in an ultrasonic machine for cleaning. Place the cleaned glass substrate in a sample holder. Place the sample holder with the glass substrate in an electron beam coating machine for vacuum treatment. When the vacuum degree reaches 4×10 -4 Pa, SiO2 and Ta3O5 were sequentially evaporated on a quartz glass substrate, 7 groups of evaporation, the evaporation rate was controlled at 0.4nm / s, the thickness of each titanium oxide layer was 63.21nm, the thickness of each Ta3O5 layer was 93.57nm, and a bottom DBR with high reflectivity (>98%) was formed.
[0047] Step 2: Dissolve the materials with a molar ratio of (FABr + MABr + GABr + CsBr) : PbBr2 = 1.15:1-1:1 in a 1 mL DMF, DMSO mixed solvent to form a 0.5 mol mL -1 A perovskite precursor solution, wherein the ratio of DMF to DMSO is 4:1, and 2-10 mg / ml of molecular additives are also added to the precursor solution.
[0048] Step 3: The bottom DBR was placed on a low temperature stage at -20 °C for 1 hour, and then a concentration of 0.5 mol mL -1, a volume of 5 μL of perovskite precursor solution was evenly dripped on the bottom DBR and then the substrate was immediately sealed in an evaporating dish with a sealing film to maintain a saturated solvent vapor environment throughout the crystallization process to prevent rapid evaporation and the formation of polycrystalline particles; because of this, the anti-solvent in Example 1 could not be used during the crystallization process. Slow crystallization was continued for 48 hours at about 5°C, and then transferred to room temperature for another 48 hours of slow crystallization. The thickness of the obtained single crystal film was about 500nm-1μm.
[0049] Step 4: 50 μL of R-MA mandelic acid chiral solution was dropped onto the perovskite single crystal film, the reaction time was 60 s, and the spin coating speed was controlled to be 5000 r / min to obtain a chiral solution post-treatment perovskite single crystal film;
[0050] Step 5: Spin-coat a PMMA optical microcavity spacer layer on the chiral solution post-processed perovskite single crystal film to enhance the cavity length. The PMMA solution concentration is 220 mg / ml, the spin-coating speed is 5000 rpm, and after spin-coating, heat on a hot stage at 120°C for 10 minutes for curing.
[0051] Step 6: Place the sample obtained in step 5 into a thermal evaporation coating machine for vacuum treatment. When the vacuum degree reaches 8×10 -4 Pa, metallic silver is evaporated on the sample with a thickness of 320nm to form a top reflective layer with a reflectivity of >99%. After the thermal evaporation is completed, the device is taken out of the evaporation chamber, and the laser device is completed.
[0052] Example 3
[0053] This embodiment introduces a method for preparing a continuous wave green chiral three-dimensional perovskite laser, and the specific steps are as follows:
[0054] Step 1: Place a 1.1 mm thick quartz glass substrate in an ultrasonic machine for cleaning. Place the cleaned glass substrate in a sample holder. Place the sample holder with the glass substrate in an electron beam coating machine for vacuum treatment. When the vacuum degree reaches 4×10 -4 Pa, SiO2 and Ta3O5 were sequentially evaporated on a quartz glass substrate, 7 groups of evaporation, the evaporation rate was controlled at 0.4nm / s, the thickness of each titanium oxide layer was 63.21nm, the thickness of each Ta3O5 layer was 93.57nm, and a bottom DBR with high reflectivity (>98%) was formed.
[0055] Step 2: Dissolve the materials with a molar ratio of (FABr + MABr + GABr + CsBr) : PbBr2 = 1.15:1-1:1 in a 1 mL DMF, DMSO mixed solvent to form a 0.5 mol mL -1A perovskite precursor solution, wherein the ratio of DMF to DMSO is 4:1, and 2-10 mg / ml of molecular additives are also added to the precursor solution.
[0056] Step 3: Evenly drop 50 μL of perovskite precursor solution on the bottom DBR; adjust the spin coating time of the coater to 60 s, control the spin coating speed to 5000 r / min, and drip chlorobenzene solution into the top hole at 30 s after starting spin coating; place the DBR with the perovskite precursor solution spin-coated on a hot stage for annealing at 100 ° C for 10 minutes to form a 100 nm thick perovskite light-emitting layer, i.e., a perovskite film.
[0057] Step 4: 50 μL of R-SA camphorsulfonic acid chiral solution was added dropwise onto the perovskite film, the reaction time was 20 s, and the spin coating speed was controlled to be 5000 r / min to obtain a chiral solution post-treatment perovskite film;
[0058] Step 5: Spin-coat a PMMA optical microcavity spacer layer on the chiral solution post-treated perovskite film to enhance the cavity length. The PMMA solution concentration is 220 mg / ml, the spin-coating speed is 5000 rpm, and after spin-coating, heat on a hot stage at 120°C for 10 minutes for curing.
[0059] Step 6: Place the sample obtained in step 5 into a thermal evaporation coating machine for vacuum treatment. When the vacuum degree reaches 8×10 -4 Pa, metallic silver is evaporated on the sample with a thickness of 320nm to form a top reflective layer with a reflectivity of >99%. After the thermal evaporation is completed, the device is taken out of the evaporation chamber, and the laser device is completed.
[0060] Example 4
[0061] This embodiment introduces a method for preparing a continuous wave green chiral three-dimensional perovskite laser, and the specific steps are as follows:
[0062] Step 1: Place a 1.1 mm thick quartz glass substrate in an ultrasonic machine for cleaning. Place the cleaned glass substrate in a sample holder. Place the sample holder with the glass substrate in an electron beam coating machine for vacuum treatment. When the vacuum degree reaches 4×10 -4 Pa, SiO2 and Ta3O5 are sequentially evaporated on a quartz glass substrate, 7 groups of evaporation, the evaporation rate is controlled at 0.4nm / s, the thickness of each titanium oxide layer is 63.21nm, the thickness of each Ta3O5 layer is 93.57nm, forming a bottom DBR reflector with high reflectivity (>98%).
[0063] Step 2: Dissolve the materials with a molar ratio of (FABr + MABr + GABr + CsBr) : PbBr2 = 1.15:1-1:1 in a 1 mL DMF, DMSO mixed solvent to form a 0.5 mol mL -1 A perovskite precursor solution, wherein the ratio of DMF to DMSO is 4:1, and 2-10 mg / ml of molecular additives are also added to the precursor solution.
[0064] Step 3: Evenly drop 50 μL of perovskite precursor solution on the bottom DBR; adjust the spin coating time of the coater to 60 s, control the spin coating speed to 5000 r / min, and drip chlorobenzene solution into the top hole at 30 s after starting spin coating; place the DBR with the perovskite precursor solution spin-coated on a hot stage for annealing at 100 ° C for 10 minutes to form a 100 nm thick perovskite light-emitting layer, i.e., a perovskite film.
[0065] Step 4: 50 μL of R-PA pyroglutamic acid chiral solution was dropped onto the perovskite film, the reaction time was 20 s, and the spin coating speed was controlled to be 5000 r / min to obtain a chiral solution post-treatment perovskite film;
[0066] Step 5: Spin-coat a PMMA optical microcavity spacer layer on the chiral solution post-treated perovskite film to enhance the cavity length. The PMMA solution concentration is 220 mg / ml, the spin-coating speed is 5000 rpm, and after spin-coating, heat on a hot stage at 120°C for 10 minutes for curing.
[0067] Step 6: Place the sample obtained in step 5 into a thermal evaporation coating machine for vacuum treatment. When the vacuum degree reaches 8×10 -4 Pa, metallic silver is evaporated on the sample with a thickness of 320nm to form a top reflective layer with a reflectivity of >99%. After the thermal evaporation is completed, the device is taken out of the evaporation chamber, and the laser device is completed.
[0068] It should be noted that other forms of gain materials (microcrystals, nanocrystals, quantum dots, etc.) are processed in the same way as the above-mentioned perovskite films and single crystals to obtain chiral luminescence and achieve laser emission.
[0069] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any researchers and technicians familiar with the field, within the technical scope described in the present invention, who make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention, should be covered by the protection scope of the present invention.
Claims
1. A continuous wave three-dimensional chiral perovskite laser, comprising an optical microcavity, a gain medium, and a spacer layer, wherein the gain medium is sandwiched between the optical microcavity and the spacer layer, and a reflective layer is plated on the spacer layer, characterized in that: The gain medium is a perovskite material or a mixed material containing a perovskite material after being treated with a chiral solution, and is uniformly distributed in the optical microcavity in the form of a thin film, microcrystal, nanocrystal, quantum dot or single crystal, with a thickness of 10nm to 1mm; The composition of the perovskite material is A'2A n-1 B n X 3n+1 Or ABX3, wherein A' is an organic amine ion, A is a monovalent cation, B is a divalent metal cation, X is an anion, and n is a positive integer; A' is phenethylamine PEA + , butylamine BA + , ethylamine EA + , S / R-p-bromo-1-phenylethylamine, S-α-methylbenzylamine, R-1-naphthylethylamine or a combination thereof; A is a cesium ion Cs + , methylamine ion MA + , formamidinium ion FA + , ethylamine ion EA + , guanidine ion GA + 、Isopropylamine ion IPA + One or more combinations thereof; B is lead ion Pb 2+ 、Sn 2+ 、Ge 2+ 、Indium ion In 2+ 、Bi ion 2+ One or more combinations of; X is a chloride ion Cl - 、Br - 、Iodide ion I - One or more combinations of; The chiral solution is prepared by dissolving a chiral inorganic material in tetrahydrofuran or isopropanol, and the chiral inorganic material is a mixture of one or more of R, S-mandelic acid, R, S-camphorsulfonic acid, and R, S-pyroglutamic acid.
2. The continuous wave three-dimensional chiral perovskite laser according to claim 1, characterized in that: The mixed material includes one or more of an organic material, a quantum dot material, an oxide material, a III-V material, a II-VI material, a rare earth material, and the perovskite material.
3. The continuous wave three-dimensional chiral perovskite laser according to claim 1, characterized in that: The type of the optical microcavity is a distributed Bragg reflector, a distributed feedback Bragg grating, a photonic crystal, a continuous bound state structure, a topological photonic crystal or a whispering gallery mode.
4. The continuous wave three-dimensional chiral perovskite laser according to claim 1, characterized in that: The spacer layer is formed of a polymer, and the polymer is polymethyl methacrylate, polyethylene glycol, polyethylene oxide or polyvinyl pyrrolidone.
5. A method for preparing a continuous wave three-dimensional chiral perovskite laser, characterized in that: For preparing a continuous wave chiral perovskite laser according to any one of claims 1 to 4, comprising: Fabrication of optical microcavities; Preparation of gain medium: A'X, AX, BX2 are mixed in a solvent to obtain a perovskite precursor solution; the perovskite precursor solution is spin-coated or drop-coated on the bottom optical microcavity, annealed, and crystallized; the chiral solution is drop-coated on the crystallized perovskite material for post-treatment to obtain a gain medium; Spin coating the polymer on the gain medium to form a spacer layer; The vacuum is applied, and a reflective layer is formed on the spacer layer by thermal evaporation.
6. The method for preparing a continuous wave three-dimensional chiral perovskite laser according to claim 5, characterized in that: On quartz, sapphire or flexible substrate polyethylene terephthalate, multiple layers of silicon dioxide / tantalum pentoxide dielectric layers are deposited by sputtering or electron beam evaporation to form a distributed Bragg reflector with high reflectivity; the thickness of each dielectric layer is λ / 4n, where λ is the central wavelength of the gain medium light emission and n is the refractive index of the dielectric layer material.
7. The method for preparing a continuous wave three-dimensional chiral perovskite laser according to claim 5, characterized in that: A metal silver film with a thickness of 200-500nm, namely a reflective layer, is deposited on the spacer layer by thermal evaporation to form a vertical microcavity surface emitting laser VCSEL structure.
8. The method for preparing a continuous wave three-dimensional chiral perovskite laser according to claim 5, characterized in that: The solvent is a mixture of any one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, and dimethylacetamide; a molecular additive is also added to the precursor solution, and the molecular additive is a mixture of one or more of polymers, small molecules, and oxides.
Citation Information
Patent Citations
Method for optimizing lead-free perovskite solar cell film
CN113206201A
Preparation method of chiral perovskite single crystal with three-dimensional structure
CN116732614A